Gorilita - Bornstein, Ruth. (New York, NY : Clarion Books, 2004)
Little Gorilla's family and friends try to help him overcome his special growing pains.
Keywords: Friendship -- Fiction; Gorilla -- Fiction; Spanish language materials; Toddler book; Board books